(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article analyzes the types of mulch materials, mulching methods, the effect of mulching on plant growth and yield, and also provides necessary information on the importance of mulching in maintaining soil moisture, controlling weeds, and stabilizing soil temperature.